Farm labor: problems and main directions of growth - Zhuravleva Ludmila; Zarubina Elena; Ruchkin Aleksey; Kruzhkova Tatyana; Ruschitskaya Olga (BIO Web of Conferences, 2022)
Increasing the productivity of farmers and the efficiency of peasant (farm) farms, including timely sales of agricultural products to the population, today they are strategically important the tasks of ensuring food security in our country. Comprehensive scientific research of farm labor in in modern conditions, highlighting problems and points of growth peasant (farm) farms, designed to help the solution of this strategic task. The article presents socio -philosophical analysis of farm labor culture in the Sverdlovsk region. The purpose of the study is defined as analysis subjective and objective factors of efficiency improvement farm labor: technical and technological equipment, logistics, motivation of economic behavior of farmers, the level of state support, as well as key issues in the activity modern farmers. To investigate the problem posed a set of theoretical and empirical methods was used: system approach, document analysis, analysis of modern foreign and domestic literature on development problems peasant (farm) farms, statistical analysis, as well as conducting a sociological study among farmers Sverdlovsk region. The results of the study, formulated in the form of recommendations, reflect the nodal points the growth of the development of peasant (farm) farms in modern difficult conditions and require taking into account such growth points in implementation of the agrarian policy of the region.